Single-cell Transcriptomics and Solid Organ Transplantation. Issue 9 (September 2019) - Malone, Andrew F.; Humphreys, Benjamin D.
Abstract : Single-cell RNA sequencing (scRNA-seq) allows the measurement of transcriptomes from individual cells providing new insights into complex biological systems. scRNA-seq has enabled the identification of rare cell types, new cell states, and intercellular communication networks that may be masked by traditional bulk transcriptional profiling. Researchers are increasingly using scRNA-seq to comprehensively characterize complex organs in health and disease. The diversity of immune cell types, some present at low frequency, in a transplanted organ undergoing rejection makes scRNA-seq ideally suited to characterize transplant pathologies because it can quantify subtle transcriptional differences between rare cell types. In this review, we discuss single-cell sequencing methods and their application in transplantation to date, current challenges, and future directions. We believe that the remarkably rapid pace of technological development in this field makes it likely that single-cell technologies such as scRNA-seq will have an impact on clinical transplantation within a decade.